The outbreak of the 2022 Russo-Ukrainian war: mental health of poles and their attitude to refugees - Babicki, Mateusz; Kowalski, Krzysztof; Mastalerz-Migas, Agnieszka (Frontiers in Public Health, 2023)
Introduction The outbreak of the Russo-Ukrainian war on 24 February 2022 has sparked a migration crisis in Europe. As a result, Poland has emerged as the country with the highest number of refugees. Due to differing social and political sentiments, this has been a significant challenge for the hitherto mono-ethnic Polish society. Methods Computer-assisted web interviews (CAWIs) were conducted with 505 Poles, mainly women with higher education from large urban centers, involved in helping refugees. Their attitudes toward refugees were assessed using an original questionnaire, while their mental health was also evaluated using the General Health Questionnaire-28 (GHQ-28). Results The vast majority of respondents reported favorable attitudes toward refugees from Ukraine. In addition, 79.2% believed refugees should be given free access to medical care, and 85% supported free access to education for migrants. Nearly 60% of respondents were not worried about their financial status due to the crisis; moreover, 40% believed that immigrants could boost the Polish economy. And 64% believed it would enrich Poland culturally. However, the majority of respondents feared infectious diseases and believed migrants should be vaccinated according to the vaccination schedule applicable in the country. Fear of war correlated positively with fear of refugees. On the GHQ-28, almost half of the respondents scored above clinical significance. Higher scores were typical for women and those fearing war and refugees. Conclusion Polish society has shown a tolerant attitude in the face of the migration crisis. The vast majority of respondents showed positive attitudes toward refugees from Ukraine. The ongoing war in Ukraine has a negative impact on the mental health of Poles, which correlates with their attitude toward refugees.